Predictors for Gangrene and Perforation of Gallbladder Wall in Patients with Acute Cholecystitis - Polina Marinova (Journal of Biomedical & Clinical Research)
Perforation of the gallbladder wall leads to a local perivesical abscess or progression to biliary peritonitis. The study aimed to analyse clinical, laboratory, and imaging indicators that have the strongest relationship with the presence of gangrenous cholecystitis and perforation of the wall and to design a predictive scoring system that highlights the risk of developing gangrenous cholecystitis with perforation. We performed a retrospective analysis of a total of 331 patients operated for five years (2016-2020) at the Department of Surgical Diseases” of Medical University - Pleven, with histologically verified chronic cholecystitis (120 patients; 36.4%), acute cholecystitis (100 patients; 30.1%), and destructive cholecystitis (111 patients; 33.5%). The statistical analysis identified nine main factors with the most substantial statistical significance in patients with gangrene and perforation of the gallbladder wall: age >65, male gender, diabetes mellitus, cardiovascular pathology, tachycardia>90 bpm, WBC>14.109, the thickness of gallbladder wall > 4 mm with pericholecystic fluid, ASAT and ALAT > 40 UI, CRP>150 ng/l. The total possible score was 11 points. The positive predictive value of the scale was 96% and identified the cases with micro-perforation and perivesical abbesses among the group with the highest total score.